Material Offshoring: Alternate Measures. (3rd April 2015) - Baldwin, John R.; Gu, Wulong; Sydor, Aaron; Yan, Beiling
Abstract : Industry measures of offshoring of material inputs are often generated using the proportionality assumption applied to aggregate import data—that the import share of each commodity used in the production process for a particular industry is similar to the import share of a commodity for the total economy. This note compares estimates of offshoring for the Canadian manufacturing sector derived using this assumption to four alternatives: two measures that use direct measures of firm‐based imports, and two hybrid measures that use both input and import information. These indirect measures are compared to survey estimates that directly assess import intensity in the production process in an effort to evaluate which indirect method yields more reasonable offshoring measures.